NOTALYZER SOFTWARE – USING POTENTIAL AT EDUCATIONAL WORK IN PROSPECT - Rusanov, S.; Ivanov, S.; Yanushkevich, O. (Journal of Information Technologies in Education (ITE), 2013)
The article deals with the research program features NOTALYZER and the possibility of its use in teaching music education. Shown that the features of this program allow you to apply it to all stages of the academic courses.